EXAMINING THE GATEWAY HYPOTHESIS OF DRUG USE IN INDONESIA - Aryo Galih Saloko; Asfi Manzilati (Indonesian Journal of Health Administration, 2021)
Background: Drug misuse is a global threat, including  in Indonesia. Solving issues of drug use is by understanding the drug patterns. One of the important concepts related to public policy in drug addiction is the gateway hypothesis. However, not all researchers support this theory as the initation of drug use is debatable in terms of how a person starts to consume tobacco and alcohol, marijuana, and then other drugs.Aim: This study identified a initiation sequence of drug use, particularly the gateway from soft to hard drugs and its reverse from hard to soft drug patterns.Methods: This study employed a dataset of drug user patients aged 14–67 years from the Rehabilitation Center of National Narcotics Board in 2014-2018. The dataset was assessed using the Addiction Severity Index (ASI). Purposive sampling was utilized in the sample selection.  The dataset was divided into three subsamples to identify the pattern. The subsamples included regular soft-drug users, regular intermediate-drug users, and regular hard-drug users. This study used a quantitative method and cross-tabulation approach along with descriptive statistics.Results: Most of the drug users began consuming intermediate drugs and then soft drugs. Only early users followed the gateway pattern, while those in the intermediate and hard drug pattern mostly did not have the gateway pattern.Conclusion: A policy about prevention of soft drug use (marijuana) in early use may be effective to reduce harder drug use in the future.Keywords: drug use, gateway hypothesis, reversal pattern